Peningkatan Hasil Belajar Fisika Melalui Pendekatan Numbered Head Together Dengan Pemberian Reward di SMP Negeri 5 Kota Jambi - Delismar Delismar (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2012)
In classical learning approach, conventional lecture method is commonly used by teachers in implementing learning process in classes.  The teacher becomes the main source of learning.  The current student’s habit that tends to be passive and individualistic resulted in a passive and monotone learning.      To overcome these problems, I was interested to implement the model of numbered heads together in learning Physics in the Class VII B of SMP Negeri 5 Kota Jambi. The purpose of this learning approach is to enable students to develop cooperative skill and more active learning of physics and to improve learning results. This research is a class action research, which were performed in two cycles.  All students’ activities in the class were observed and recorded in observation sheet, consisting of teacher observation sheet and student observation sheet. To find out the learning outcomes, formative test was performed using a written instrument form.  The results show the increase of students’ discipline, cooperation, liveliness, timeliness in learning Physics.  In addition, the learning model also increases the students’ learning outcomes. The average learning results increased to 75.38 (increase 3.25 points).  To conclude, the implementation of Number Head Together increase students’ discipline, cooperation, activities, and timeliness.  The model also increase the Physics learning outcome of student in SMP Negeri 5 Kota  Jambi.